Contemplation and Leadership: In the Footsteps of Fr. Yves Raguin, S.J. - Duraj, Jarosław (Macau Ricci Institute Public Forum, 2021)

Fr. Yves Raguin, S.J. and Interreligious Dialogue - Duraj, Jaroslaw (Macau Ricci Institute Public Forum, 2023)

Re-thinking Chinese Ecumene in the Global Age - Duraj, Jaroslaw (Eric Voegelin’s Asian Political Thought, 2020)
The rise of Asia in global affairs has forced western thinkers to rethink their assumptions, theories, and conclusions about the region. Eric Voegelin’s Asian Political Thought brings together a mixture of established and rising scholars from both Asia and the West to reflect upon the political philosopher’s thought about China, Japan, Korea, Central Asia, and India. From Voegelin’s writings, readers will not only understand how Voegelin’s approach can illuminate the fundamental principles and issues about Asia but also what are the challenges and possibilities that Asia offers in the twentieth-first century. For those who want to move past the superficial commentary and clichés about Asia, Eric Voegelin’s Asian Political Thought is the book for you.

The Role of Metaxy in the Political Philosophy of Eric Voegelin - Duraj, Jarosław (Peter Lang US, 2021)
This book is a study of Eric Voegelin (1901-1985) and of the role played by metaxy in his vision of political philosophy. Metaxy, already defined by Plato as the "in-between" matrix of the human condition, is for Voegelin a powerful notion that symbolizes the intermediate state in which man experiences diverse and opposing tensions such as the ones between immanence and transcendence or mortality and immortality. The metaxy constitutes the realm of the divine-human mutual participation (methexis), and its locus resides in human consciousness (nous), there where the divine reality manifests itself as the origin of being. Being the field of intermediation between opposing forces, man has to keep the balance of consciousness in order to differentiate the noetic and pneumatic dimensions and so attune his life to the divine ground of being. This book claims that for Voegelin metaxy shapes the possibility of the philosophical, historical, political and religious orientation in life. Indeed, Voegelin’s approach deserves recognition as an option adequate for addressing the intellectual challenges engendered by modern and postmodern philosophies.